La autoestima como factor de incidencia en el proceso formativo de los educandos del subnivel básica media en el periodo 2016-2017 - Bustillos Cayo, Verónica Alexandra (2017)
The main objective of this research was to determine the self - esteem incidence in the educational process at students of the basic sub - level in "Quito" Elementary School in 2016 - 2017. This purpose arises as a response to a problem that has become chronic in all country educational institutions and in particular in the under study institution; Where the self-esteem decline in students has become a factor of negative impact on interpersonal relationships, academic performance and the formative process. Through the methodology developed in this process, a mixed approach research is applied, that is, quantitative and qualitative, being the bibliographic and the field work the basic process modalities; the descriptive type research was applied too. For data collection, the interview and the survey techniques were used, and through the question guide and the questionnaire instruments. The project results expose great shortcomings of the different educational actors; Weaknesses that must be overcome through the managers responsible commitment, teachers and parents; empowering the conclusions and punctually assuming the recommendations made in the final report section, so that the project meets the purpose, relevance and contribution initially planned.